2013
DOI: 10.1682/jrrd.2012.10.0181
|View full text |Cite
|
Sign up to set email alerts
|

Power mobility with collision avoidance for older adults: User, caregiver, and prescriber perspectives

Abstract: Abstract-Collision avoidance technology has the capacity to facilitate safer mobility among older power mobility users with physical, sensory, and cognitive impairments, thus enabling independence for more users. Little is known about consumers' perceptions of collision avoidance. This article draws on interviews (29 users, 5 caregivers, and 10 prescribers) to examine views on design and utilization of this technology. Data analysis identified three themes: "useful situations or contexts," "technology design i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
13
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(17 citation statements)
references
References 46 publications
4
13
0
Order By: Relevance
“…This notion is in keeping with previous research where participants in a long-term care facility recognized that collision avoidance would help to prevent accidents [23]. Interestingly, participants in another study suggested that an IPW could be used for training purposes for individuals who are having difficulty learning to drive a PW, which may improve skill and decrease accidents [15].…”
Section: Decreased Risk Of Accidents While Participating In Social Acsupporting
confidence: 82%
See 2 more Smart Citations
“…This notion is in keeping with previous research where participants in a long-term care facility recognized that collision avoidance would help to prevent accidents [23]. Interestingly, participants in another study suggested that an IPW could be used for training purposes for individuals who are having difficulty learning to drive a PW, which may improve skill and decrease accidents [15].…”
Section: Decreased Risk Of Accidents While Participating In Social Acsupporting
confidence: 82%
“…Further, navigating in small spaces, such as elevators, narrow store aisles and public bathrooms, was also voiced as a challenge to social participation that may be mitigated by use of the path following/obstacle avoidance feature. Participants in the study by Wang et al [15] shared these perspectives where collision avoidance was identified as being useful in busy and unpredictable environments, such as dining rooms, stores, hallways and sidewalks, as well as for the purpose of backing up.…”
Section: Increased Social Participation Opportunitiesmentioning
confidence: 99%
See 1 more Smart Citation
“…However, negative obstacles constitute major physical barriers for safe power wheelchair driving. Indeed, a study in the form of regular users interviews, carers emphasized the difficulties encountered with curbsides [6]. In this context, driving assistance in outdoor environments would be expected to provide more safety while driving in an environment consisting of negative obstacles.…”
Section: Introductionmentioning
confidence: 99%
“…They are often designed for a specific manufacturer, which limits the possible variety of wheelchairs and adaptations [5]. † The number of people who could benefit from a smart wheelchair is large and growing [10][11].…”
Section: Introductionmentioning
confidence: 99%